PENGARUH PENDIDIKAN KEWIRAUSAHAAN, NEED FOR ACHIEVEMENT, DAN INTERNAL LOCUS OF CONTROL TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 1 SUKOHARJO - Wahyu Eko Saputro; Bambang Wasito Adi; Salman Alfarisy Totalia (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
The research objective to be achieved in this study is to determine the effect of the variables of entrepreneurship education, need for achievement, and internal locus of control on entrepreneurial interest. This research is a quantitative study with a population of 358 students and a sample of 189 in class XII students of SMKN 1 Sukoharjo from proffesional competences, namely Online Business and Marketing, Accounting and Financial Institutions, Automatication of Office Management, and Computer and Network Engineering. Proportionate random sampling is a technique used in sampling. Data were collected using a Likert scale with a closed questionnaire and using multiple regression analysis for data analysis. The results showed that there was a simultaneous or partial influence of the variables of entrepreneurship education, need for achievement, and internal locus of control on entrepreneurial interest. Adjusted R square has a value of 0.673 which shows that 67.3% entrepreneurial interest is influenced by entrepreneurship education, need for achievement, and internal locus of control and the remaining 32.7% is influenced by other variables. This shows that the relationship of entrepreneurial interest with the three independent variables is very strong because the value is greater than 0.50. Results sffective contribution to entrepreneurship education is 46.2%, need for achievement is 8.8%, and internal locus of control is 12.9% towards entrepreneurial interest.